Application of RADAR Corner Reflectors for the Detection of Small Vessels in Synthetic Aperture Radar - Stastny, J.; Cheung, S.; Wiafe, G.; Agyekum, K.; Greidanus, H. (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2015)
Detection of vessels from space-based synthetic aperture radar (SAR) data is an important area of research with many applications, including fisheries monitoring, counter-piracy, and maritime border security. The detection of vessels on the ocean surface in SAR imagery requires that the vessel has sufficiently high radar cross section (RCS). In general, the RCS of an object is a function of the object's material, size, and shape, as well as RADAR parameters such as center frequency. Even, two objects of the same size may have different RCSs based on construction materials (i.e., wood versus metal). In Ghana, as in much of the Gulf of Guinea, wooden canoes 6-25 m in length represent a significant percentage of maritime traffic. These canoes are not easy to detect and track in coastal RADAR, nor are they easily detected in SAR imagery. These vessels may represent a significant risk to maritime safety and security. Here, we describe one possible solution for the problem described-above based on inexpensive, versatile corner reflectors with high RCS. Specifically, we describe the design and construction of high RCS corner reflectors and results from a series of experiments in which corner reflectors were installed on wooden canoes. During the experiments, canoes were deployed to specific locations off the coast of Ghana at specific times, corresponding to the acquisition of space-based SAR imagery. We present results from these experiments, which indicate that wooden canoes with these corner reflectors can be detected in space-based SAR imagery. © 2008-2012 IEEE.
Keywords: Maritime domain awareness; small vessel detection; synthetic aperture radar (SAR)